The Autobiographical Basis of the Novel "Handan" by Halide Edib Adıvar - AVAGYAN, ANZHELA (Bulletin of Yerevan University B: Philology, 2021)
In the article, referring to the novel “Handan” by Halide Edib Adıvar, the author, by making comparisons between the epic biography of the main heroine and the life of Halide Edib, states the autobiographical genre of the novel. The author also presents, that this is one of the first novels by Halide Edib, where she expressed her feministic ideas.